Contemporary Art and Contemporary Sport in the Arabian Peninsula. Issue 3 (2nd July 2020) - Edgar, Andrew
ABSTRACT: This paper explores the relationship between the development of art and sport in the Arabian Peninsula. In particular, it will be argued that both sport and art can be understood in terms of a trajectory from the 'modern' to the 'contemporary'. Modernity and modernism are introduced through an interpretation of Paul Delaunay's series of paintings 'The Cardiff Team' (1912–22) which may be read as an expression of modernity. The content of the paintings documents core elements of European modernist culture, including technology and science, leisure, consumerism and advertising, and crucially (international) sport. Delaunay's work provides a background from which to reflect upon the development of sport into something like its contemporary form, in early 20th Europe. By drawing on Terry Smith's analysis of the difference between modern and contemporary art, and applying this to sport, in order to suggest that there is a distinctive contemporary form of sport, the core tensions within both artistic and sporting practices are argued to lie in the movement from a conception of sport as an expression of modernity, where this is conceived as a universal movement, exemplified by Western humanism, towards a conception of sport as something particularised, expressive of local cultures. The promotion of art institutions and sports events within the Arabian Peninsula highlights the resultant tensions between the neo-colonial influence of Western culture and the reinterpretation of that culture, locally, in order to reflect upon and articulate communal identity within the contexts of globalism and transnationalism.